From Pietro Ellero to Enrico Ferri: the genesis of penalistica sociale: Peer reviewed article (Italian Review of Legal History, 2021)
This article treats the genesis of the penalistica sociale that emerged in the last two decades of the nineteenth century, which was a movement of jurists who showed great sensitivity to the social dimension of law and who attributed a decisive role to social factors in the generation of crime. The first part of the article will focus on the definition of penalistica sociale and the overcoming of the label ‘legal socialism’; then the different contributions made to penalistica sociale by Pietro Ellero and Enrico Ferri will be examined. The two authors can be considered the precursors of penalistica sociale.
Keywords: penalistica sociale; legal socialism; Pietro Ellero; Enrico Ferri; criminal law 19th century